(untitled) (Baghdad Science Journal, 2016)
This study focuses on diagnosis of Candida species causing Vulvovaginal Candidiasis using phenotype and genotype analyzing methods, and frequencies of candida species also using Vulvovaginal Candidiasis patients. 130 samples (100 from patients and 30 from non infected women) were collected and cultured on biological media. Identifying the yeasts, initially some phenotypic experiments were carried out such as germ tube, from motion of pseudohyphae and clamydospores in CMA+TW80 medium, API20 candida and CHROMagar Candida. Genomic DNA of all species were extracted and analyzed with PCR and subsequent Polymerase Chain Reaction - Restriction Fragments Length Polymorphism (PCR-RFLP) methods. Frequency of C. albicans, C. krusei, C. tropicalis , C. parapsilosis and C. glabrata were 46.4%, 31%, 18%, 7.2%, and 1.8%, respectively.The ITS1-ITS4 region was amplified and the Restriction enzyme Msp1 digests this region and was used to identify of candida species .Electrophoretically ribosomal DNA of C. albicans, C. krusei, C. tropicalis and C. glabrata produced two bands whereas the C. parapsilosis gave one band.